Prevalence of metabolic risk factors and associated 10‐year prediction of cardiovascular disease and diabetes in female employees. (September 2014) - Gray, Benjamin J; Bracken, Richard M; Turner, Daniel; Morgan, Kerry; Mellalieu, Stephen D; Thomas, Michael; Williams, Sally P; Williams, Meurig; Rice, Sam; Stephens, Jeffrey W; On behalf of the Prosiect Sir Gâr Group
Abstract Cardiovascular disease (CVD) and type 2 diabetes (T2DM) remain two of the greatest health challenges in the United Kingdom. Guidelines currently advocate screening individuals to identify those at 'high risk' (10‐year risk ≥20%) of CVD and T2DM. This study examined the prevalence of undiagnosed risk factors associated with these two conditions and predicted 10‐year risk. Female local health board employees (n = 371) with no prior diagnosis of CVD or T2DM accepted an invitation for a workplace‐based health assessment. Demographic, anthropometric, systolic and diastolic blood pressure, family and medical histories were all recorded and capillary blood samples obtained for analysis of total and HDL cholesterol and HbA1c. Ten‐year CVD and T2DM risk were predicted using the QRISK2 and QDiabetes algorithms, respectively. A significant proportion of females were either overweight (37.2%) or obese (23.5%), coupled with a high percentage with central obesity (77.6%). Systolic hypertension (42.0%), diastolic hypertension (39.4%) and/or reduced HDL concentrations (32.6%) were also prevalent in a large number of female workers. However, <1% of all workers were at 'high risk' of CVD and only 3.2% were predicted to be at 'high risk' of developing T2DM in the next 10 years. The vast majority of females assessed were at 'low risk' (<10%) of either CVD or T2DM. Despite strong evidence of metabolic risk factors observed in female employees, only a small proportion of workers were predicted to be at 10‐year high risk of either CVD or T2DM. Copyright © 2014 John Wiley & Sons, Ltd.